PENGARUH STRES KERJA TERHADAP KINERJA PERAWAT MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA RUMAH SAKIT WIJAYA KUSUMA KABUPATEN LUMAJANG JAWA TIMUR) - Riza, Maulana Muhammad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Abstract: This study was conducted at Hospital Wijaya Kusuma Kabupaten Lumajang, in order to determine the direct effect on the performance of job stress, work stress on job satisfaction, job satisfaction on the performance, as well as the indirect effect of work stress on performance through job satisfaction of nurses. The study design used is Explanatory research, nurse number in Wijaya Kusuma Hospital is 44, because the population is small then all nurses are taken as respondents. Methods of data collection in this study using a questionnaire measured by scale linkert. Data analysis using descriptive data analysis techniques and analysis Partial Least Square (PLS). Results of this study are: (1) Work Stress significant effect on performance Nurse, (2) Work Stress no significant effect on job satisfaction Nurse, (3) Job Satisfaction significant effect on performance Nurse, (4) Work Stress does not affect indirectly of the nurses performance through job satisfaction. This shows that the hospital has not been able to control the Wijaya Kusuma Work Stress in nurses, although job satisfaction of nurses who perceived effect on the nurses performance. Â Key words: Work Stress, Job Satisfaction, Performance.